2022
DOI: 10.1177/1753495x211041899
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis in pregnancy: Systematic review and case series

Abstract: Background Myasthenia gravis is an autoimmune disease which can impact pregnancy. Methods Six databases were systematically searched for studies with at least five subjects reporting pregnancy outcomes for women with myasthenia gravis in pregnancy. Assessment of bias was performed for all included studies. Forty-eight cases from our own centre were also included in the analysis. Results In total, 32 publications met inclusion criteria for systematic review, for a total of 33 unique data sets including 48 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…It was further reported that there was a significant risk of women delivering through CS with Crohn’s disease (OR 1.65 (1.19–2.29)) but not as much with ulcerative colitis (OR 1.30 (0.86 to 1.96)) [ 33 , 34 , 112 ]. One of the reviews conducted a narrative analysis and reported women with myasthenia gravis are at increased risk of requiring assisted vaginal delivery or CS compared to women without the condition (population size = 854) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was further reported that there was a significant risk of women delivering through CS with Crohn’s disease (OR 1.65 (1.19–2.29)) but not as much with ulcerative colitis (OR 1.30 (0.86 to 1.96)) [ 33 , 34 , 112 ]. One of the reviews conducted a narrative analysis and reported women with myasthenia gravis are at increased risk of requiring assisted vaginal delivery or CS compared to women without the condition (population size = 854) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conditions like multiple sclerosis are known to have an adverse effect on pregnancy outcomes, but evidence is sparse to support this [ 29 , 36 ]. Some autoimmune conditions have been studied more than others with inconsistent findings [ 37 , 38 ]. This umbrella review aims to consolidate evidence from systematic reviews of the association of common autoimmune conditions with pregnancy outcomes in order to identify the strength and precision of these associations.…”
Section: Introductionmentioning
confidence: 99%
“…Rate of C-section was 38.3% in our cohort. Mode of delivery in MG patients shows great variability across studies that might be explained by geographical and temporal disparities as well as variances in the level of care provided by the hospitals where birth was given (5,7,18). A recent nationwide Swedish register-based cohort study found higher elective caesarian section rate in MG patients compared to matched controls (19).…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal myasthenia occurs in around 10% of the newborn children of mothers with MG [ 8 , 36 ]. The babies have transient muscle weakness that rarely affects the respiratory muscles.…”
Section: Methodsmentioning
confidence: 99%